Gender differences in response to cyberostracism, and Twitter as a virtual aid to the socially excluded. - Francis, Kevin Joseph. (2010)
According to Goleman (2006), we are social beings and we have a basic need for belongingness and acceptance amongst our peers. Unfortunately, social interaction is a reciprocal activity and there are instances where people are neglected or ignored in their social realm. Social exclusion is a phenomenon that has prevailed throughout evolution. This study is focused on a new sphere of social exclusion, cyberostracism, and its effects on gender. With the proliferation of the Internet technology, the experience of social exclusion has taken on a cyber-perspective. Analysis of the experience of cyberostracism in this study supports previous findings that the experience of social exclusion does encourage individuals to engage in promotion-focused behavior, but no support for gender effects was found.